1996
DOI: 10.1002/(sici)1097-0096(199609)24:7<355::aid-jcu5>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of the wall thickness of the lower uterine segment in patients with previous cesarean section

Abstract: In pregnant women with a history of cesarean section, wall thickness of the lower uterine segment may help determine the risk and safety of vaginal delivery. Determination of wall thickness may help identify the potential risk of uterine rupture in pregnant women who do not wish to have another cesarean section or who are not eligible for surgery due to other systemic disorders. In this study, 50 pregnant women with previous cesarean sections were evaluated with ultrasound preoperatively, and measurements of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…The review comprises 12 studies published between 1988 and 2009 [12,[33][34][35][36][37][38][39][40][41][42][43] including together 1834 women with a previous low transverse caesarean hysterotomy who underwent ultrasound measurement of the thickness of the lower uterine segment at [35][36][37][38][39][40] gestational weeks. In seven of the 12 studies the full lower uterine segment thickness was measured [12,33,36,[38][39][40]42], in four studies the myometrial thickness was measured [34,35,37,43], and in one study both measurements were taken [41].…”
Section: Gestational Weeks Predict Uterine Rupture or Dehiscence?mentioning
confidence: 99%
See 3 more Smart Citations
“…The review comprises 12 studies published between 1988 and 2009 [12,[33][34][35][36][37][38][39][40][41][42][43] including together 1834 women with a previous low transverse caesarean hysterotomy who underwent ultrasound measurement of the thickness of the lower uterine segment at [35][36][37][38][39][40] gestational weeks. In seven of the 12 studies the full lower uterine segment thickness was measured [12,33,36,[38][39][40]42], in four studies the myometrial thickness was measured [34,35,37,43], and in one study both measurements were taken [41].…”
Section: Gestational Weeks Predict Uterine Rupture or Dehiscence?mentioning
confidence: 99%
“…In seven of the 12 studies the full lower uterine segment thickness was measured [12,33,36,[38][39][40]42], in four studies the myometrial thickness was measured [34,35,37,43], and in one study both measurements were taken [41]. Because only three of the 12 studies reported the frequency of uterine rupture separately, the outcome measure was "uterine rupture or uterine dehiscence", i.e.…”
Section: Gestational Weeks Predict Uterine Rupture or Dehiscence?mentioning
confidence: 99%
See 2 more Smart Citations
“…Qureshi et al reported ≤ 2 mm as the criterion for poor healing of the uterine 8 . Preoperative ultrasound measurements of the lower uterine segment wall thickness also correlated well with the true intraoperative situs 9 .…”
Section: Ultrasound Finding and Operative Management Of A Uterine Rupmentioning
confidence: 99%